Association of Pulmonary Hypertension and Monoclonal Gammopathy of Undetermined Significance. (18th November 2022) - Lyle, Melissa A.; Bhatia, Subir; Fenstad, Eric; Schroeder, Darrell; McCully, Robert B.; Lacy, Martha Q.; Feyereisn, Wayne
Abstract : Objective . To determine the prevalence of monoclonal gammopathy of undetermined significance (MGUS) in patients with PH as well as precapillary PH. Methods . Olmsted County residents with PH, diagnosed between 1/1/1995 and 9/30/2017, were identified, and age and sex were matched to a normal control group. The PH group and normal control group were then cross-referenced with the Mayo Clinic MGUS database. Charts were reviewed to verify MGUS and PH. Heart catheterization data were then analyzed in these patients for reference to the gold standard for diagnosis. Results . There were 3419 patients diagnosed with PH by echocardiography between 1995 and 2017 in Olmsted County that met the criteria of our study. When the PH group ( N  = 3313) was matched to a normal control group (3313), a diagnosis of MGUS was significantly associated with PH 10.2% (OR = l.84 [95% CI 1.5–2.2], p < 0.001 ), compared with controls 5.8% based on echo diagnosis. Using heart catheterization data (484 patients), a diagnosis of MGUS was associated with PH 13.0% (OR = 3.94 [95% CI 2.28–6.82], p < 0.001 ). For pulmonary artery hypertension ( N  = 222), a diagnosis of MGUS was associated with PH at similar 12.2% (OR = 4.50 [95%CI 1.86–10.90], p < 0.001 . Conclusions . There is a higher prevalence of MGUS in patients with PH and precapillary PH compared with normal controls. This association cannot be explained fully by other underlying diagnoses associated with PH. Assessing for this in patients with PH of unclear etiology may be reasonable in the workup of patients found to have PH.